2005
DOI: 10.1016/j.otohns.2005.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term histological outcomes of injected autologous fat into human vocal folds after secondary laryngectomy

Abstract: Our liposuctioned autologous fat injection histologically offered long-term improvement in patients with impaired glottal closure from vocal fold paralysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
0
8

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 8 publications
3
18
0
8
Order By: Relevance
“…There was also a statistically sig- The improvement in voice quality parameters observed in this study is consistent with those in previous studies. [5][6][7][8] For instance, a study on 33 patients with UVCP in Taiwan observed that jitter had improved from 2.7 at baseline to 1.3 at month 3, 5 which is comparable with our observed effect size. Hartl and colleagues also observed that acoustic parameters (eg, jitter and shimmer) reduced quickly after one month of surgery and maintained up to 24 months.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…There was also a statistically sig- The improvement in voice quality parameters observed in this study is consistent with those in previous studies. [5][6][7][8] For instance, a study on 33 patients with UVCP in Taiwan observed that jitter had improved from 2.7 at baseline to 1.3 at month 3, 5 which is comparable with our observed effect size. Hartl and colleagues also observed that acoustic parameters (eg, jitter and shimmer) reduced quickly after one month of surgery and maintained up to 24 months.…”
Section: Resultssupporting
confidence: 90%
“…The improvement in voice quality parameters observed in this study is consistent with those in previous studies . For instance, a study on 33 patients with UVCP in Taiwan observed that jitter had improved from 2.7 at baseline to 1.3 at month 3, which is comparable with our observed effect size.…”
Section: Discussionsupporting
confidence: 92%
“…Various studies have reported the absorption rates between 6 months and 2.5 years. [21] In spite of this, our results and those reported in other such studies are encouraging. The longstanding good vocal outcome would not necessarily mean nonabsorption of fat, but it could also be due to good compensation over time or recovery of vocal cord parlaysis.…”
Section: Discussionsupporting
confidence: 61%
“…Histology revealed viable adipocytes with a minimal inflammatory response in both patients. The authors concluded that, even though there is debate about the negative effects of liposuction compared to those of fat obtained by the open technique, the liposuction technique can keep the fatty tissue viable 18 . However, it was not possible to determine the amount of fat that survived in the two larynges studied since the injected volume was not measured, so that the result—presence of viable adipocytes—was of little clinical significance.…”
Section: Discussionmentioning
confidence: 99%
“…There was no statistically significant difference in histologic findings between the groups submitted to the three types of treatment, i.e., use of insulin, grafting by endoscopic injection, and grafting by an open technique. Indeed, there is no consensus about this topic, with some studies showing an almost total loss of fat 4,16 mainly by liposuction, and others reporting surprising results 18,19 . In view of the countless variables involved, it is always very difficult to determine what really modifies the capacity for fat survival.…”
Section: Discussionmentioning
confidence: 99%